Biographical Note Josefa Toledo de Aguerri (1866 – 1962) - Estrada, Camila (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Bibliographical note on the educator Josefa Toledo de Aguerrí, who displays, through her life and work, the trajectory of modern pedagogy in the context of the modernizing Nicaraguan project.